2010
DOI: 10.3724/sp.j.1001.2010.03501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Approach of Subjective Trust Based on Cloud Model

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Some researchers put forward evolutionary algorithms combined trust mechanisms [30], [31]. Wang et al [32] proposed the trust assessment method based on the cloud model. Xie et al [33] designed the double excitation and deception detection based trust model.…”
Section: B Trust Management Strategiesmentioning
confidence: 99%
“…Some researchers put forward evolutionary algorithms combined trust mechanisms [30], [31]. Wang et al [32] proposed the trust assessment method based on the cloud model. Xie et al [33] designed the double excitation and deception detection based trust model.…”
Section: B Trust Management Strategiesmentioning
confidence: 99%
“…The fuzzy AHP theory is used which is based on entropy weight mechanism. Wagng et al [34] have suggested that the existing approaches which are based on probability and fuzzy set theory didn't give enough importance to uncertainty. To eliminate this problem, the authors have proposed a quantifiable subjective trust evaluation approach.…”
Section: Fuzzy Logic Based Trust Model In Cloudmentioning
confidence: 99%
“…Wang et al [40] proposed a subjective trust quantification evaluation method based on a cloud model. The method introduced three digital characteristics of subjective trust to quantify on object's trust and the changes of object trust were described by a mutative trust cloud.…”
Section: Trust Modelmentioning
confidence: 99%